An Interesting Case Series of Actinomyces odontolyticus and Lactobacillusplantarum Infection in A Tertiary Care Hospital in New Delhi - Arpita Panda; Bhawna Sharma (RGUHS Journal of Medical Sciences)
Anaerobic bacteria like Actinomyces odontolyticus and Lactobacillus plantarum are part of normal flora in the oral cavity gastrointestinal tract and genitourinary tract. However it can be pathogenic in immunocompromised patients and or seriously ill patients. Hence distinguishing an anaerobe as a commensal or a pathogen in a particular sample can be challenging. With complete patient history four pus samples were received from 3 patients in Robertsons cooked meat RCM media. RCM was inoculated on three plates namely Neomycin anaerobic sheep blood agar for anaerobic incubation in a Gas Pack Jar and sheep blood agar for aerobic incubation in a CO2 incubator and aerobically at 37deg C. No growth on the aerobically and CO2 incubated plate. Neomycin anaerobic sheep blood agar plates showed growth confirmed by VITEK-2 along with manual tests and sensitivity testing was done by using the pour plate method using Epsilon meter strips. Four isolates were identified. In two cases A. odontolyticus and in the other two cases L. plantarum were confirmed. All four isolates were resistant to the metronidazole drug. Since metronidazole resistance is rising among anaerobic infections judicious use of this drug is advocated and antibiotic sensitivity testing of anaerobes should be done before starting treatment.